Peripheral Lung Squamous Carcinoma With ROS1 Rearrangement Sensitive to Crizotinib: A Case Report - Yang, Guangdie; Wang, Jie; Yao, Yinan; Zhao, Jun; Yu, Zheyan; Gao, Qiqi; Ye, Jiani; Ma, Wenjiang (Frontiers in Oncology, 2021)
ROS1 rearrangements have been identified as driver mutations, accounting for 1–2% of lung adenocarcinoma, but are extremely rare in case of lung squamous cell carcinoma. In this work, we report a lung squamous cell carcinoma in a patient with peripheral lung cancer radiological manifestation, harboring ROS1 rearrangement, with high sensitivity to crizotinib. Our findings suggest that clinicians should pay more attention toward the occurrence of ROS1 rearrangements and the application of crizotinib for lung squamous cell carcinoma treatment.